2020
DOI: 10.1177/000313482008600428
|View full text |Cite
|
Sign up to set email alerts
|

Use of CT Scans for Abdominal Pain in the ED: Factors in Choice

Abstract: Overutilization of healthcare resources is a threat to long-term healthcare sustainability and patient outcomes. CTis a costly but efficient means of assessing abdominal pain; however, 97 per cent of ED physicians acknowledge its overutilization. This study sought to understand factors that influence ED providers’ decision regarding CT use in the evaluation of abdominal pain. After evaluating a patient for acute abdominal pain, ED providers filled in a form in which the primary diagnosis and index of suspicion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Despite CT scan resulting in the correct clinical diagnosis up to 87% of the time of patients with non-traumatic abdominal pain in the emergency department, 38 it is currently utilized for only about 54% of patients presenting with these symptoms. 39 Increase utilization of CT scan in patients with abdominal pain and relevant risk factors could be 1 way to decrease the incidence of missed AAA and aortic dissections in the emergency department. As reflected with a higher prevalence of "other CV misdiagnosis" for aortic dissections, initial misdiagnosis of acute myocardial infarction in patients with dissections also remains a concern.…”
Section: Discussionmentioning
confidence: 99%
“…Despite CT scan resulting in the correct clinical diagnosis up to 87% of the time of patients with non-traumatic abdominal pain in the emergency department, 38 it is currently utilized for only about 54% of patients presenting with these symptoms. 39 Increase utilization of CT scan in patients with abdominal pain and relevant risk factors could be 1 way to decrease the incidence of missed AAA and aortic dissections in the emergency department. As reflected with a higher prevalence of "other CV misdiagnosis" for aortic dissections, initial misdiagnosis of acute myocardial infarction in patients with dissections also remains a concern.…”
Section: Discussionmentioning
confidence: 99%
“…Race and ethnicity were not reported in any of our 13 included studies, making assessment of disparities in these domains impossible. Outside of the studies identified by our systematic search, other studies have documented disparities in ED CT imaging based on insurance status, 120 race, and ethnicity 120–122 . Patients with Medicaid are 20% less likely than privately insured patients to undergo CTAP for acute abdominal pain (not specifically recurrent pain or repeat CTAP) 120 .…”
Section: Questionmentioning
confidence: 99%
“…Outside of the studies identified by our systematic search, other studies have documented disparities in ED CT imaging based on insurance status, 120 race, and ethnicity. [120][121][122] Patients with Medicaid are 20% less likely than privately insured patients to undergo CTAP for acute abdominal pain (not specifically recurrent pain or repeat CTAP). 120 Black and Hispanic patients are 42% to 52% less likely than White patients to undergo CTAP for acute abdominal pain.…”
Section: Decision Criteria and Additional Considerationsmentioning
confidence: 99%
See 2 more Smart Citations